-5v+25=-3(v-9)

Simple and best practice solution for -5v+25=-3(v-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5v+25=-3(v-9) equation:


Simplifying
-5v + 25 = -3(v + -9)

Reorder the terms:
25 + -5v = -3(v + -9)

Reorder the terms:
25 + -5v = -3(-9 + v)
25 + -5v = (-9 * -3 + v * -3)
25 + -5v = (27 + -3v)

Solving
25 + -5v = 27 + -3v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '3v' to each side of the equation.
25 + -5v + 3v = 27 + -3v + 3v

Combine like terms: -5v + 3v = -2v
25 + -2v = 27 + -3v + 3v

Combine like terms: -3v + 3v = 0
25 + -2v = 27 + 0
25 + -2v = 27

Add '-25' to each side of the equation.
25 + -25 + -2v = 27 + -25

Combine like terms: 25 + -25 = 0
0 + -2v = 27 + -25
-2v = 27 + -25

Combine like terms: 27 + -25 = 2
-2v = 2

Divide each side by '-2'.
v = -1

Simplifying
v = -1

See similar equations:

| 3z^3-8z^2=0 | | -20=4(u-6)-8u | | 6-4.5-6= | | 9z^3-64z=0 | | 2/3t-16=62 | | 3(a+14)=6(2a+3) | | -19=-3+4w | | 6x-2k+8=x+5 | | 8n^2=6 | | 294=18-y | | 35y^2-9y+3=0 | | 284=18-y | | 2m^2+27m-4=0 | | 2n+3=4n-7 | | 1.75x=4.2 | | 6n+12=20 | | 2m^2=10-2m | | (n+3)(2n+3)=0 | | 10+9x=10+x | | x^2+y^2+2*x+14*y-15=0 | | 2n^2=105-11n | | 10x-17=2x+10 | | 5.7-6/12 | | x(a-6b)=3m(x-c) | | 0=-16t+40t-84 | | 26-m=76 | | g(x)=x^5-9x^3 | | 6(15-3x)=120 | | -3(x+5)=-30 | | y=4(a)+3+2 | | 8(2+x)=80 | | 12321+231756= |

Equations solver categories